One-year mental health outcomes in a cohort of COVID-19 survivors. (January 2022) - Mazza, Mario Gennaro; Palladini, Mariagrazia; De Lorenzo, Rebecca; Bravi, Beatrice; Poletti, Sara; Furlan, Roberto; Ciceri, Fabio; Rovere-Querini, Patrizia; Benedetti, Francesco; ,; Vai, Benedetta; Bollettini, Irene; et al.
Abstract: COVID-19 survivors are at increased risk of persistent psychopathology after the infection. Despite long-term sequelae are an increasing concern, long-term neuropsychiatric consequences remain largely unclear. This cohort study aimed at investigating the psychopathological impact of COVID-19 in Italy one year after infection, outlining the trajectory of symptomatology at one, six-, and twelve-months follow-up. We evaluated 402, 216, and 192 COVID-19 survivors respectively at one, six, and 12 months. A subgroup of 95 patients was evaluated longitudinally both at one, six, and 12 months. Validated self-report questionnaires were administered to assess depression, fatigue, anxiety, and post-traumatic distress. Socio-demographics and setting of care information were gathered for each participant. At six and twelve months, respectively 94 (44%) and 86 (45%) patients self-rated in the clinical range in at least one psychopathological dimension. Pathological fatigue at twelve months was detected in 63 patients (33%). Considering the longitudinal cohort an interaction effect of sex and time was observed for depression (F = 8.63, p < 0.001) and anxiety (F = 5.42, p = 0.005) with males showing a significant increasing trend of symptoms, whereas an opposite course was observed in females. High prevalence of psychiatric sequelae six and 12 months after COVID-19 was reported for the first time. These findings confirm the need to provide integrated multidisciplinary services to properly address long-lasting mental health sequelae of COVID-19 and to treat them with the aim of reducing the disease burden and related years of life lived with disability.